Pengaruh Kepemimpinan Transformasional dan Motivasi Kerja terhadap Kinerja Karyawan dengan Perilaku Kerja Inovatif sebagai Variabel Mediasi pada Pegawai Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kabupaten Muaro Jambi - Fathiyah Fathiyah; Zulfina Andriani; Fitriaty Fitriaty (Universitas Batanghari Jambi, 2022)
This study aims to determine the effect of transformational leadership and work motivation on employee performance with innovative work behavior as a mediating variable for employees of the Investment and One Stop Service Office of Muaro Jambi Regency. The research method used is a quantitative method, and the data collection technique uses a questionnaire with a Likert scale. The population is 47 employees of the State Civil Apparatus and Honorary Employees of the Investment and One Stop Service Office of Muaro Jambi Regency. Technical Data Analysis using Partial Least Sguare (PLS). The results of the study found that (1) transformational leadership affects employee performance, (2) work motivation affects employee performance, (3) transformational leadership affects innovative work behavior, (4) work motivation affects innovative work behavior, (5) leadership Transformational effect on employee performance is mediated by innovative work behavior and (6) work motivation affects employee performance mediated by innovative work behavior. The suggestions in this study are that in order to apply Transformational Leadership in an organization, it is necessary to pay attention to the way leaders communicate with their subordinates and improve good relations with subordinates. And it is also suggested to the Education and Training Center to include Transformational Leadership material in Leadership Training III and IV.